Evaluation of postoperative changes in vascularized iliac bone grafts used for mandibular reconstruction. Issue 8 (August 2018) - Noguchi, T.; Sarukawa, S.; Tsuchiya, Y.; Okada, N.; Hayasaka, J.; Sasaguri, K.; Nishino, H.; Jinbu, Y.; Mori, Y.
Abstract: Vascularized iliac bone grafts are used for mandibular reconstruction, but the factors affecting graft maintenance are unknown. This study explored the postsurgical changes in vascularized iliac bone grafts in patients who had undergone mandibular reconstruction after segmental resection. The study involved 24 patients (16 men and eight women) with oral tumours or osteoradionecrosis. Thirteen patients required bare bone grafting (BBG) and 11 patients required reconstruction with soft tissue coverage (six with a skin paddle and five with direct closure). The bone graft maintenance rate (with regard to the height of the centre of the graft) was calculated immediately after surgery and at 3, 6, 12, 24, and 36 months after surgery. The maintenance rate was significantly lower in the BBG group than in the soft tissue coverage group at 3, 6, 12, 24, and 36 months, and in those who were fitted with dentures compared to those who were not at 6, 12, 24, and 36 months. Local infection also influenced the maintenance rate, but not significantly so. These findings indicate that the reconstruction technique and denture use can affect the bone graft maintenance rate after mandibular reconstruction with vascularized iliac bone grafts.